2012
DOI: 10.1007/s11357-012-9415-9
|View full text |Cite
|
Sign up to set email alerts
|

Aging and substitutive hormonal therapy influence in regional and subcellular distribution of ERα in female rat brain

Abstract: Estrogens are not only critical for sexual differentiation it is well-known for the role of 17β-estradiol (E2) in the adult brain modulating memory, learning, mood and acts as a neuroprotector. E2 exerts its actions through two classical receptors: estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ). The distribution of both receptors changes from one brain area to another, E2 being able to modulate their expression. Among the classical features of aging in humans, we find cognitive impairment, deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 80 publications
2
8
0
Order By: Relevance
“…One potential explanation could be that although brain production and concentration of estradiol decreases after ovariectomy, jugular E2 is not decreased because of a parallel decrease of estradiol use or catabolism. It has been shown that ovariectomy induces a down-regulation of estrogen receptors in the diencephalon, and this effect was reversed with estradiol treatment (Navarro et al, 2013). Moreover, ovariectomy down-regulates estrogen catabolism in rodent peripheral tissues (Ghraf et al, 1975a; Ghraf et al, 1975b) and the enzymes responsible for this catabolism are found in the periphery and in the brain of birds (Ambadkar and Kotak, 1978; Bhujle and Nadkarni, 1976; Matsunaga et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation could be that although brain production and concentration of estradiol decreases after ovariectomy, jugular E2 is not decreased because of a parallel decrease of estradiol use or catabolism. It has been shown that ovariectomy induces a down-regulation of estrogen receptors in the diencephalon, and this effect was reversed with estradiol treatment (Navarro et al, 2013). Moreover, ovariectomy down-regulates estrogen catabolism in rodent peripheral tissues (Ghraf et al, 1975a; Ghraf et al, 1975b) and the enzymes responsible for this catabolism are found in the periphery and in the brain of birds (Ambadkar and Kotak, 1978; Bhujle and Nadkarni, 1976; Matsunaga et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It must also be stressed that it is not likely that the down-regulation of the ERa protein seen in the present study upon EB administration is consequent to the inability of the ERa antibody to recognize the protein. In fact, the ERa antibody used in this study was generated to the C-terminal sequence of the rat ERa and recognizes both bound and unbound ERa, as shown in immunohistochemical and Western blot studies of the rat telencephalon (Mora´n et al, 2013;Navarro et al, 2013), pituitary (Sosa et al, 2013) and uterus (Baranda-Avila et al, 2013) where, using the same antibody, it was demonstrated that estradiol administration either does not change or up-regulates ERa expression.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that G protein-coupled receptors are likely to down-regulate with chronic E 2 treatment (Cheng et al 2005, Hatsumi & Yamamuro 2006, but this is not always the case (Navarro et al 2013). In addition, some studies have found ERa to be located in the cell membrane, and these cell membrane ERs will be faster acting than nuclear ERs.…”
Section: Some Caveatsmentioning
confidence: 99%